DYNAMICS OF PROCALCITONIN AT THE PATIENT AFTER COMBINED ORGAN TRANSPLANTATION - M. Sh. Khubutia; V. P. Nikulina; A. V. Pinchuk; M. A. Godkov (Вестник трансплантологии и искусственных органов, 2010)
Case report represents two episodes of procalcitonin elevation in dynamics, connected with different induction mechanisms of this sepsis marker at the patient after combined pancreas and kidney transplantation.